Triage Patterns for Medicare Patients Presenting to Nontrauma Hospitals With Moderate or Severe Injuries. Issue 2 (February 2015) - Mohan, Deepika; Barnato, Amber E.; Rosengart, Matthew R.; Angus, Derek C.; Wallace, David J.; Kahn, Jeremy M.
Abstract : Objective: To understand hospital-level variation in triage practices for patients with moderate-to-severe injuries presenting initially to nontrauma centers. Background: Many patients with moderate-to-severe traumatic injuries receive care at nontrauma hospitals, despite evidence of a survival benefit from treatment at trauma centers. Methods: We used claims from the Centers for Medicare and Medicaid Services to identify patients with moderate-to-severe injuries who presented initially to nontrauma centers. We determined whether or not they were transferred to a level I or II trauma center within 24 hours of presentation, and used multivariate regression to assess the influence of hospital-level factors on triage practices, after adjusting for differences in case mix. Results: Transfer of patients with moderate-to-severe injuries to trauma centers occurred infrequently, with significant variation among hospitals (median 2%; interquartile range 1%–6%). Greater resource availability at nontrauma centers was associated with lower rates of successful triage, including the presence of neurosurgeons (relative reduction in transfer rate: 76%, P < 0.01), more than 20 intensive care unit beds (relative reduction 30%, P < 0.01) and a high resident-to-bed ratio (relative reduction 23%, P < 0.01). However, patients were more likely to survive if they presented to hospitals with higher triage rates (odds of death for patients cared for at hospitals with the highest tercile of triage rates, compared with lowest tercile: 0.92; 95% confidence interval: 0.85–0.99, P = 0.02). Conclusions: Injured Medicare beneficiaries presenting to nontrauma centers experience high rates of undertriage, determined in part by increasing availability of resources. Care at hospitals with low rates of successful triage is associated with worse outcomes. Abstract : We performed a retrospective cohort study of hospital-level triage rates for patients with moderate-to-severe traumatic injuries presenting initially to nontrauma hospitals. We quantified variation in triage practices, identified characteristics associated with performance, and assessed the effect of performance on patient outcomes.